Is a Perceived Activity-Friendly Environment Associated with More Physical Activity and Fewer Screen-Based Activities in Adolescents? - Kopcakova, Jaroslava; Dankulincova Veselska, Zuzana; Madarasova Geckova, Andrea; Bucksch, Jens; Nalecz, Hanna; Sigmundova, Dagmar; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of environmental research and public health, 2017)
Background: The aim of this study is to explore if perception of an activity-friendly environment is associated with more physical activity and fewer screen-based activities among adolescents. Methods: We collected self-reported data in 2014 via the Health Behavior in School-aged Children cross-sectional study from four European countries (n = 13,800, mean age = 14.4, 49.4% boys). We explored the association of perceived environment (e.g., "There are other children nearby home to go out and play with") with physical activity and screen-based activities using a binary logistic regression model adjusted for age, gender, family affluence and country. Results: An environment perceived as activity-friendly was associated with higher odds that adolescents meet recommendations for physical activity (odds ratio (OR) for one standard deviation (SD) change = 1.11, 95% confidence interval (CI) 1.05-1.18) and lower odds for excessive screen-based activities (OR for 1 SD better = 0.93, 95% CI 0.88-0.98). Conclusions: Investment into an activity-friendly environment may support the promotion of active life styles in adolescence.
Keywords: Environment; odds ratio; Sedentary Behavior; Europe; Female; Perception; ženské pohlaví; sedavý životní styl; průřezové studie; Adolescent; percepce; lidé; Evropa; cvičení; screen-based activities; physical activity; Cross-Sectional Studies; Male; Social Environment; sociální prostředí; životní prostředí; mužské pohlaví; perceived activity-friendly environment; adolescence; Exercise; mladiství; Odds Ratio; Humans